Anisotropic photoemission time delays close to a Fano resonance - Claudio Cirelli (Nature Portfolio, 2018)
Ionization time delays are of interest in understanding the photoionization mechanism in atoms and molecules in ultra-short time scales. Here the authors investigate the angular dependence of photoionization time delays in the presence of an autoionizing resonance in argon atom using RABBITT technique.